Elevated circulating endothelial-specific microRNAs in migraine patients: A pilot study. (August 2018) - Cheng, Chun-Yu; Chen, Shih-Pin; Liao, Yi-Chu; Fuh, Jong-Ling; Wang, Yen-Feng; Wang, Shuu-Jiun
Background: Evidence of vascular dysfunction in migraine is increasing. MicroRNAs (miRs) have emerged as important regulators of vascular endothelial functions. This exploratory study investigated whether circulating levels of miRs associated with endothelial function are altered in migraine patients. Methods: Thirty patients with migraine (20–50 years old) without overt vascular risk factors and 30 sex- and age-matched healthy controls participated. The levels of four miRs that regulate endothelial function (miR-155, miR-126, miR-21, and Let-7g) were quantified and expressed in terms of fold changes (2 −ΔΔct ) relative to mean levels in the control group. Associations of miRs levels with headache features and syncope comorbidity were explored. Results: Compared to controls, migraine patients had upregulated expression of miR-155 (6.17-fold, p = 0.018), miR-126 (6.17-fold, p = 0.013), and let-7g (7.37-fold, p = 0.005). Levels of miR-155 (r = 0.375, p = 0.041) and miR-126 (r = 0.375, p = 0.041) were associated with syncope frequency in the past year in migraine patients. Migraine patients with aura have insignificant higher expression of miRs levels compared to those without. Conclusions: In this pilot study, circulating levels of endothelial-specific miRs appear to be elevated in migraine patients and may be associated with syncope comorbidity.